Rationalizing Small‐Molecule Donor Design toward High‐Performance Organic Solar Cells: Perspective from Molecular Architectures. Issue 11 (24th August 2018) - Han, Guangchao; Yi, Yuanping
Abstract: Tuning donor/acceptor interfacial arrangements and electron‐transfer processes in the active layers is crucial to improve the performance of organic solar cells (OSCs). Here, the impact of different molecular architectures (i.e., A–π–D–π–A, D–π–A–π–D and π–A–D–A–π) of the donors on the interfacial arrangements and electronic processes in small‐molecule (SM) OSCs is elucidated by means of multiscale theoretical simulations. An A–π–D–π–A structured donor with sizable terminal units, extended π bridges, and bulky side groups on the backbone core is proved to be able to simultaneously obtain both efficient charge generation and migration as well as suppressed charge recombination, thus paving the way for the rational design of electron donors toward high‐performance SM OSCs. Abstract : An A–π–D–π–A structure with sizable terminal units (to increase close contacts with electron acceptors and facilitate charge generation), extended π bridges (to promote hole transport), and bulky side chains on the backbone core (to prevent acceptors to approach the core and reduce charge recombination) is demonstrated to be an effective strategy for the design of electron donors toward high‐performance small‐molecule organic solar cells.